2014
DOI: 10.1016/j.tvjl.2014.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Empathic veterinarians score cattle pain higher

Abstract: The treatment of cattle pain often relies upon veterinarians. The aim of this study was to qualify the influence of veterinarians skills, attitudes, and empathy on cattle pain assesment and consequently disbudding pain management. A web-based questionnaire was sent to Finnish veterinary students in either the preclinical or clinical stage, and also to production-animal practice oriented veterinarians. The questionnaire recorded demographics, statements of opinions, pain scoring of cattle conditions and procedu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
63
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 32 publications
(55 reference statements)
3
63
2
3
Order By: Relevance
“…However, this was somewhat contradictory to our previous finding in which veterinarians oriented toward production-animal practice and young veterinarians treat disbudding pain in calves according to national recommendations, with sedatives, local anesthetics, and NSAIDs (Norring et al, 2014). Obviously, education of Finnish veterinarians working in the field could be improved further.…”
Section: Figurecontrasting
confidence: 81%
See 1 more Smart Citation
“…However, this was somewhat contradictory to our previous finding in which veterinarians oriented toward production-animal practice and young veterinarians treat disbudding pain in calves according to national recommendations, with sedatives, local anesthetics, and NSAIDs (Norring et al, 2014). Obviously, education of Finnish veterinarians working in the field could be improved further.…”
Section: Figurecontrasting
confidence: 81%
“…Veterinarians agree that disbudding is painful (Hewson et al, 2007;Hudson et al, 2008;Norring et al, 2014) but not all veterinarians alleviate pain before disbudding (Huxley and Whay 2006;Hewson et al, 2007;Misch et al, 2007). It is recommended to use sedatives, local anesthetics, and NSAID to alleviate disbuddingrelated pain (AVA, 2004;New Zealand Government, 2005; AVMA, 2012), but little is known about how well veterinarians follow these recommendations.…”
Section: Introductionmentioning
confidence: 99%
“…In group of affected cows was found higher speed of feeding compare to healthy. Significant differences in feeding speed during the period, when cows were affected with lameness found Michie and Andonovic (2015).…”
Section: Figurementioning
confidence: 90%
“…Janssen et al (2015) observed that incidence of claw diseases has impact on the animals´ needs and that the pain limits animal locomotion, what result in decrease of trough visits as well as reduced feeding time, increase of the feeding rate and prolonged lying time. Michie and Andonovic (2015), Thorup et al (2015) confirmed the influence of lameness on feed intake during the day.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation